Empowerment of MSMEs Kube Lestari and Ngudi Mulyo through the Universitas Ahmad Dahlan PMM Program: Implementing Technopreneurship and Digital Marketing Strategies - Robi'in, Bambang Robi'in,; Prathisara, Gibbran; Pungkiawan, Pius Rino; Hakiki, Qori Alfiani; Aliyah, Himatul (CV. Rayyan Dwi Bharata, 2026)
The Community Empowerment Program by Students (PMM) of Universitas Ahmad Dahlan was conducted in Triwidadi Village, Pajangan Subdistrict, Bantul Regency, in collaboration with two local MSME partners, Kube Lestari and Ngudi Mulyo. The program aimed to enhance entrepreneurial capacity and strengthen the competitiveness of local products through a technopreneurship and digital marketing approach. Based on the situational analysis, both partner groups showed strong economic potential in the production of emping and palm sugar but faced challenges in production management, business governance, and digital promotion. The implementation consisted of five stages: socialization, training, technology application, mentoring, and evaluation for sustainability. The training covered topics on online advertising strategies, packaging design, product branding, and promotional photography, involving MSME members from two hamlets—Polaman and Butuh Kidul. The results indicated significant improvements in partners’ abilities to design better packaging, utilize social media and online marketplaces, and create engaging digital promotional content. Furthermore, participants demonstrated increased motivation and confidence in managing their businesses and expanding their markets through technology-based solutions. Overall, the program successfully fostered independence and professionalism among local MSMEs, guiding them toward a sustainable model of digital entrepreneurship.